القيمة التنبؤية لمشعر خباثة أورام المبيض - الدالي, عصام; عبد الرحمن, أحمد; زريق, هلا (Latakia University Journal -Medical Sciences Series, 2019)
Objective : Ovarian cancer leads to 184,000 deaths worldwide. The discriminatting between benign and malignant ovarian tumors is very important for optimal management , as the amount of postoperative residual tumor is one of most important prognostic factors . This study aimed to evaluate the ability of four risk of malignancy indices (RMI) to detect malignant ovarian tumors before surgery Methods : This prospective study enrolled a total of 75 women admitted to the Department of Obstetrics and Gynecology in Tishreen University Hospital for surgical exploration of pelvic masses.The sensitivity, specificity, negative and positive predictive values and diagnostic accuracy of four RMIs to diagnose malignant ovarian tumors, were obtained. The Receiver Operating Characteristic (ROC) curves for RMI 1, RMI 2, RMI 3, and RMI 4 were calculated to compare the accuracy. Results : Using a cut-off level of 200 to indicate malignancy for RMI 1, RMI 2 and RMI 3, and using a cut-off level of 450 to indicate malignancy for RMI 4. The RMI 2 gave the highest sensitivity (83.3%) while the RMI1, RMI 3 and RMI 4 gave the sensitivity of 70-76.6%. The RMI 4 gave the highest specificity (86.6%) while the RMI 1, RMI 2 and RMI 3 gave the specificity of 77.7-84.4%. The positive predictive value of the four methods was 71.8-76.9% and the negative predictive value of the four methods was 79.6-87.8%. For the ROC curve, the greatest area under curve (AUC) was associated with the RMI 2 values (0.879) as compared to the ROC values for the RMI 1(0.850), RMI 3 (0.832), and RMI 4(0.841). Conclusion : The RMI is able to discriminate between benign and malignant ovarian tumors. The RMI 2 was the most reliable in predicting malignancy in terms of area under the curves. The RMI method is a valuable, applicable and simple technique that can be used in clinical practice. أهمية وهدف البحث : يؤدي سرطان المبيض إلى وفاة184 ألف امرأة سنوياً. إن التمييز بين الأورام المبيضية السليمة والخبيثة قبل الجراحة أمر هام للغاية وذلك من أجل تحقيق أفضل معالجة جراحية ممكنة, إذ يعتبر الحجم المتبقي من الورم بعد الجراحة من أهم العوامل الانذارية .تم إجراء هذه الدراسة لتقييم قدرة مشعرات خطر الخباثة الأربعة (RMI) في كشف الأورام المبيضية الخبيثة قبل الجراحة . طرق البحث : شملت هذه الدراسة المستقبلية 75 مريضة تم قبولهن في قسم التوليد و أمراض النساء في مستشفى تشرين الجامعي لإجراء فتح بطن جراحي باستطباب كتلة حوضية مبيضية في عامي 2018-2019. تم حساب الحساسية , النوعية , القيمة التنبؤية الإيجابية , القيمة التنبؤية السلبية و دقة التشخيص لمشعرات خطر الخباثة الأربعة لتشخيص الأورام المبيضية الخبيثة , تم حساب منحنى خاصية المشغل المتلقي (ROC) لكلٍّ من (RMI 1 , RMI 2 , RMI 3 , RMI 4) لمقارنة الدقة التشخيصية. النتائج: قمنا باستخدام القيمة الحدية 200 لتحديد الخباثة في كلٍّ من المشعرات RMI 1 , RMI 2 , RMI 3 , و استخدام القيمة الحدية 450 لتحديد الخباثة في RMI 4 . أظهر RMI 2 أنّه يملك أعلى حساسية (83,3%) في حين أعطت المشعرات RMI 1 , RMI 3, RMI 4 حساسيةً ما بين 70– 76.6% . بالمقابل أظهرRMI 4 أنّه يملك أعلى نوعية (86,6%) في حين أعطت المشعرات RMI3 , RMI 2, RMI 1 نوعيةً ما بين 77,7–84,4% . تراوحت القيمة التنبؤية الإيجابية للمشعرات الأربعة ما بين 71,8-76,9% .فيما يخص منحنى ROC , ترافقت أفضل مساحة تحت المنحنى (AUC) مع قيم RMI 2 (0,879) , مقارنةً مع قيم ROC لكل من RMI 1 (0.850) , RMI 3 (0.832) , و RMI 4 (0.841) . الخلاصة : إنّ مشعر خطر الخباثة قادر على التمييز بين الأورام المبيضية الخبيثة والحميدة . أظهر المشعر RMI 2 أنّه الأفضل في التنبؤ بالخباثة وفقاً للمساحة تحت المنحنى . RMI هو طريقة بسيطة ,غير مكلفة و يمكن تطبيقها بسهولةٍ في الممارسة السريرية.